1999
DOI: 10.1128/mcb.19.12.7897
|View full text |Cite
|
Sign up to set email alerts
|

Protein trans-Acting Factors Involved in Ribosome Biogenesis in Saccharomyces cerevisiae

Abstract: 2The synthesis of ribosomes is one of the major cellular activities, and in eukaryotes, it takes place primarily, although not exclusively, in a specialized subnuclear compartment termed the nucleolus (125, 155). There, the rRNA genes are transcribed as precursors (pre-rRNAs), which undergo processing and covalent modification. Maturation of pre-rRNAs is intimately linked to their assembly with the ribosomal proteins (r-proteins). These processes depend on various cis-acting elements (6, 188), and they require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
343
1
15

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(366 citation statements)
references
References 210 publications
6
343
1
15
Order By: Relevance
“…Depletion of Bms1p causes defects in rRNA processing at cleavage sites A 0 , A 1 , and A 2 + A: Structure of 35S pre-rRNA (upper portion) and a simplified scheme of pre-rRNA processing in yeast (lower portion)+ Processing sites and intermediates are indicated+ For more details, see Kressler et al+ (1999) and Venema and Tollervey (1999)+ B: Northern blotting and primer extension analysis of RNA isolated from WT and GAL::bms1 strains grown in YPGal (lanes 0) or YPD6% for 6, 12, 22, or 44 h+ The oligonucleotide probes, indicated on the scheme of the 35S pre-rRNA above the gels, were complementary to: 59ETS, upstream of A 0 (a); ITS1, upstream of A 2 (b); ITS1, between A 2 and A 3 (c); ITS1, downstream of A 3 (d); ITS2, upstream of C 2 (e); mature 25S rRNA (f ); and mature 18S rRNA (g)+ Positions of different processing intermediates and mature rRNAs are indicated. In b, the 22S RNA is only visible after prolonged exposure (not shown)+ Elevated levels of physiological precursors 35S and 27SA 2 in the WT strain after transfer to YPD6% are likely caused by higher pre-rRNA production rates during growth in the rich medium containing 6% glucose and supplemented with 20 mg/mL adenine+ h: Primer extension products ending at sites ϩ1 (59 end of the 35S precursor), A 0 , A 2 , and B 1L /B 1S +…”
Section: Bms1p Immunoprecipitates Low Levels Of U3 Snornamentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of Bms1p causes defects in rRNA processing at cleavage sites A 0 , A 1 , and A 2 + A: Structure of 35S pre-rRNA (upper portion) and a simplified scheme of pre-rRNA processing in yeast (lower portion)+ Processing sites and intermediates are indicated+ For more details, see Kressler et al+ (1999) and Venema and Tollervey (1999)+ B: Northern blotting and primer extension analysis of RNA isolated from WT and GAL::bms1 strains grown in YPGal (lanes 0) or YPD6% for 6, 12, 22, or 44 h+ The oligonucleotide probes, indicated on the scheme of the 35S pre-rRNA above the gels, were complementary to: 59ETS, upstream of A 0 (a); ITS1, upstream of A 2 (b); ITS1, between A 2 and A 3 (c); ITS1, downstream of A 3 (d); ITS2, upstream of C 2 (e); mature 25S rRNA (f ); and mature 18S rRNA (g)+ Positions of different processing intermediates and mature rRNAs are indicated. In b, the 22S RNA is only visible after prolonged exposure (not shown)+ Elevated levels of physiological precursors 35S and 27SA 2 in the WT strain after transfer to YPD6% are likely caused by higher pre-rRNA production rates during growth in the rich medium containing 6% glucose and supplemented with 20 mg/mL adenine+ h: Primer extension products ending at sites ϩ1 (59 end of the 35S precursor), A 0 , A 2 , and B 1L /B 1S +…”
Section: Bms1p Immunoprecipitates Low Levels Of U3 Snornamentioning
confidence: 99%
“…In eukaryotic cells, synthesis and processing of ribosomal RNAs (rRNAs) and assembly of ribosomes occur in the nucleolus and follow an unusually complex pathway+ The 18S, 5+8S, and 25-28S rRNAs are synthesized as a single precursor (pre-rRNA), which contains additional sequences that are discarded during RNA maturation+ The maturation process involves extensive modification of rRNA nucleotides, most of them guided by small nucleolar RNAs (snoRNAs), followed by multiple cleavage events resulting in the formation of different processing intermediates+ The substrate for rRNA processing is a large ribonucleoprotein complex containing a multitude of ribosomal proteins and accessory nucleolar trans-acting factors that associate with the nascent pre-rRNA (reviewed by Kressler et al+, 1999;Venema & Tollervey, 1999;Lewis & Tollervey, 2000)+ rRNA processing has been most extensively studied in the yeast Saccharomyces cerevisiae and many trans-acting factors, both proteins and ribonucleoproteins, required for the process have been characterized+ These include, in addition to guide snoRNAs, the ribonucleoprotein RNase MRP, the essential snoRNAs U3, U14, snR30 and snR10, and many proteins, which either act in association with snoRNAs or function independently+ Among the latter are putative ATPdependent RNA helicases, Dim1p methylase, and endoand exoribonucleases (Kressler et al+, 1999;Venema & Tollervey, 1999)+ Despite substantial progress in identification of the trans-acting factors required for pre-rRNA processing, their precise functions remain largely unknown+ The factor best characterized to date is the U3 snoRNP+ Based on results from yeast and vertebrate systems, it appears that U3 snoRNP plays a central role in the assembly of the machinery responsible for processing of 18S rRNA and biogenesis of the 40S ribosomal subunit (Beltrame & Tollervey, 1992;Mougey et al+, 1993;Venema & Tollervey, 1999;Borovjagin & Gerbi, 2000, and references therein)+ U3 snoRNA base pairs with the 35S pre-rRNA within the 59 external transcribed spacer (ETS) and the 59 part of 18S rRNA and is required for early cleavages at the processing sites A 0 , A 1 , and A 2 (Beltrame & Tollervey, 1995;Sharma & Tollervey, 1999;Venema & Tollervey, 1999, and references therein)+ The yeast U3 snoRNP has recently been shown to contain five strongly associated structural proteins (Watkins et al+, 2000)+ However, consistent with the central role of U3 snoRNP in rRNA maturation, immunoprecipitation (IP) experiments revealed many additional proteins associating with the particle+ These include Sof1p, Mpp10p, Imp3p, Imp4p, Dhr1p, Lcp5p, and Rcl1p (Jansen et al+, 1993;Dunbar et al+, 1997;Wiederkehr et al+, 1998;Lee & Baserga, 1999;…”
Section: Introductionmentioning
confidence: 99%
“…The pool of 79 RPs are actively transcribed by RNA polymerase II, exported to the cytosol for translation and imported to the nucleolus for assembly (Lempiainen and Shore, 2009). In addition, there are a suite of auxiliary factors that assist in the processing of rRNA, assembly of the small and large subunits and finally export and maturation of the functional ribosome (Kressler et al, 1999;Venema and Tollervey, 1999) (Figure 1). Considering that this process is predicted to use 460% of resources in the cell (Warner, 1999), it stands to reason that the coordinated activities of ribosome synthesis would be subject to extensive quality control surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleolus of eukaryotic cells contains a wide array of stable small nucleolar RNPs (snoRNPs) involved in processing of ribosomal RNA transcripts and in ribosome assembly (Kressler et al+, 1999;Venema & Tollervey, 1999)+ The most abundant of the snoRNPs required for processing of pre-rRNA, the U3 snoRNP, has been studied in a number of different organisms+ Functional studies on the role of the U3 snoRNA in mice, Xenopus laevis, or Saccharomyces cerevisiae have revealed that the U3 snoRNA is required for pre-18S rRNA processing (Kass et al+, 1990;Savino & Gerbi, 1990;Hughes & Ares, 1991;Mougey et al+, 1993;Borovjagin & Gerbi, 1999)+ In yeast cells, the U3 snoRNA base pairs with the pre-rRNA at two sites and is required for endonucleolytic cleavage at sites A0, A1, and A2 leading to 18S rRNA production (Hughes & Ares, 1991;Beltrame & Tollervey, 1992, 1995Beltrame et al+, 1994;Hughes, 1996;Sharma & Tollervey, 1999)+ Comparison of the U3 snoRNAs among eukaryotic organisms has revealed several conserved sequence elements called boxes A, A9, B, C, C9, and D (Fig+ 1A;Wise & Weiner, 1980;Jeppesen et al+, 1988;Porter et al+, 1988;Tyc & Steitz, 1989;Kiss & Solymosy, 1990;Myslinski et al+, 1990;Hughes & Ares, 1991;Marshallsay et al+, 1992;Tycowski et al+, 1993)+ Secondary structure models for the U3 snoRNA have been proposed from a variety of U3 molecules based on computer folding, phylogenetic sequence comparison, and chemical and enzymatic mapping; yet, no consensus structure has emerged (Kiss et al+, 1985;Hughes et al+, 1987;Parker & Steitz, 1987;Jeppesen et al+, 1988;Porter et al+, 1988;Kiss & Solymosy, 1990;Myslinski et al+, 1990;…”
Section: Introductionmentioning
confidence: 99%